Konsep kredit dalam bingkai pemikiran Zaid bin Ali serta relevansinya di era kontemporer - Ismail, Ismail; Amini, Salisa; Misrah, Misrah (AL-Muqayyad, 2024)
Humans continuously engage in various activities, encompassing both divine obligations (hablumminallah) and social interactions (hablumminannas). Islam provides clear guidance on permissible credit transaction schemes and prohibits those that lead to riba. This study employs a descriptive qualitative approach, analyzing the thoughts of Zaid bin Ali through a review of journal articles published on Google Scholar. The research aims to explore Zaid bin Ali's perspective on the concept of credit in Islamic economics and to analyze its relevance to contemporary Islamic financing practices. The findings reveal that, according to Zaid bin Ali, credit transactions with higher prices than cash payments are permissible, provided they are based on mutual agreement and consent between the parties involved. This perspective aligns with the practices of Islamic financial institutions, as regulated by DSN MUI Fatwa No. 04/DSN-MUI/2000.